Tremendum Et Fascinans Transformasi Wujud Rangda Sebagai Ide Penciptaan Karya Drawing - Nugraha, Putri Rakanita; Cahyana, Agus; Wahyudi, Nandang Gumelar (ATRAT: Jurnal Seni Rupa, 2025)
Rangda is a Balinese folklore with strong symbolic meaning and a source of inspiration in artistic expression. The creation of this work raises the transformation of the Rangda form as an idea for the creation of drawing works with the approach of interpretation and reinterpretation. Charcoal is used expressively to create a different form of Rangda, by further translating the author’s inner experience into the form of the work. This work will take the form of visual progression panels, with each panel connected to the other to display a complete flow. An expressionist approach is used to express the deep emotion, horrific atmosphere, and transformation of the Rangda figure in the drawing. The charcoal medium was chosen for its ability to present sharp contrasts, expressive, dark, and dramatic strokes. The creation of this work is a process to understand and translate the author’s inner experience, with the hope of realizing it into a ‘horrifying’ and mesmerizing visual work.